2017
DOI: 10.24996/ijs.2017.58.2c.3
|View full text |Cite
|
Sign up to set email alerts
|

Detection The Prevalence of Adhesins and Extracellular hydrolytic enzymes genes in Candida albicans Biofilm Formation

Abstract: Biofilm formation (BF) is one of the most important virulence factors of Candida spp. The aim of this study was to detect the prevalence of genes responsible in biofilm formation of C. albicans by conventional PCR technique. Among 49 vaginal specimens (VC), C. albicans was the most predominant species in percentage 22/49 (45%) and 27(55%) were non albicans. Out of 47 oral specimens (OS), 22/47(47%) were C. albicans, whereas 25(53%) were non albicans. At the present study; all C. albicans were biofilm producers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The current investigation concurred with Mohammed et al (2017) who discovered that all C. albicans isolates tested developed biofilm on polystyrene with varying strength.…”
Section: Molecular Identification Of C Albicanssupporting
confidence: 88%
“…The current investigation concurred with Mohammed et al (2017) who discovered that all C. albicans isolates tested developed biofilm on polystyrene with varying strength.…”
Section: Molecular Identification Of C Albicanssupporting
confidence: 88%
“…Unfortunately, techniques like single and direct PCR or multiplex PCR have not been widely adopted despite being more sensitive and specific and having a quicker turnaround time [30]. Earlier studies showed that the expression of HWP1 and genes from the ALS, SAP, LIP, and PLB gene families is connected to the development of biofilm on mucosal surfaces [24]. Fungal species that belong to Cryptococcus, Candida, Aspergillus, Histoplasma, and Pneumocystisare are responsible for more than 90% of all reported fungal-related deaths [25].…”
Section: Conventionalmentioning
confidence: 99%